Rule-governed behavior: an experimental study of augmenting rules - Ferreira, Andressa; Gonçalves, Laura Lima Fichtler; Modenesi, Rafael Diego (Perspectivas em Análise do Comportamento, 2023)
The aim of the present study was to assess whether a rule of the augmental type, composed of qualifying autoclitics, would alter the function of initially neutral stimuli to reinforcers. Nineteen adults participated in the study. In Phase 1, two initially neutral consequential stimuli (meaningless words VIC and ZED) were used as consequences for choices in a simultaneous simple discrimination task. In Phase 2, rules composed of qualifying autoclitics (e.g., “VIC is correct, ZED is incorrect”) were presented with the aim of establishing a reinforcing function for the stimulus that was produced by responses with lower frequency in Phase 1, and responses in the simultaneous simple discrimination task were evaluated again in Phase 3. Comparing the results of Phases 1 and 3, eight participants showed an increase of over 80% in choices of stimuli related to the consequential stimulus specified by the rule as “correct” after Phase 2; four exhibited this performance only after being reintroduced to Phases 2 and 3, and seven did not achieve this performance. Thus, it is possible to assert that the presentation of the rule partially worked to alter the function of two initially neutral stimuli. Explanations for the difficulty of 11 participants in achieving this performance are discussed, and suggestions for future studies are proposed.